2021
DOI: 10.1080/03019233.2021.1911770
|View full text |Cite
|
Sign up to set email alerts
|

A review: research progress of flux pellets and their application in China

Abstract: The flux pellets as the burden materials of blast furnace have been widely investigated and used. However, its research and practical applications keep slowly developing in China due to the historical status of the sinter and the limitation of raw material condition. The sinter output is constrained by the environmental department due to its great emission of air pollutants. Therefore, enhancing the development of pellets becomes an urgent task for China's steel enterprises. Flux pellets shows excellent adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Magnesian flux pellet has become a high-quality and efficiency blast furnace raw material with high grade, low energy consumption and environmental protection 2-4 . According to statistics, compared with sintering process, pollutants CO 2 , SO 2 and NO x produced by tons of products in pelletizing process were reduced respectively by 75%, 53% and 16%, and energy consumption in pelletizing process was reduced by 11.9% 5,6 . Therefore, pelletizing process was more environmental friendly than sintering process.Production processes of pellets mainly included shaft furnace, belt roaster and grate rotary kiln [7][8][9] .…”
mentioning
confidence: 99%
“…Magnesian flux pellet has become a high-quality and efficiency blast furnace raw material with high grade, low energy consumption and environmental protection 2-4 . According to statistics, compared with sintering process, pollutants CO 2 , SO 2 and NO x produced by tons of products in pelletizing process were reduced respectively by 75%, 53% and 16%, and energy consumption in pelletizing process was reduced by 11.9% 5,6 . Therefore, pelletizing process was more environmental friendly than sintering process.Production processes of pellets mainly included shaft furnace, belt roaster and grate rotary kiln [7][8][9] .…”
mentioning
confidence: 99%
“…With the reduction from hematite to magnetite and wustite, the volume expansion change of the iron ores can be expressed as Fe 2 O 3 (100%)→Fe 3 O 4 (124%)→FeO (131%)→Fe (126%). [ 11 ] The required volume increase for oriented growth of magnetite (111) planes parallel to hematite (0001) planes and associated internal cracks developed normal to these planes, which causes the volume expansion of iron ores during the reduction process. [ 12 ] When the degree of low‐temperature reduction degradation is serious, the amount of the reducing gas passing through the burden column decreases, and then the pressure difference inside the blast furnace increases and the reduction efficiency decreases; even the smooth operation of blast furnace could be influenced negatively.…”
Section: Introductionmentioning
confidence: 99%
“…; moreover, the higher RI means a higher indirect reduction percentage, lower coke rate, and higher productivity in the blast furnace. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has mainly concentrated on the characterization, as well as pelletizing and sintering behaviors, of pure iron ores and manganese ores with very high Mn/Fe mass ratios [ 15 , 16 , 17 , 18 , 19 ]. Faria et al investigated the high-temperature disintegration of a Brazilian rich manganese lump ore and roasted pellets and found that the pellets demonstrated better mechanical and metallurgical properties than the natural lump ore [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%